Incorporation of decision-maker preferences in an interactive evolutionary multi-objective algorithm using a multi-criteria sorting - Cruz-Reyes, Laura; Fernández, Eduardo; Sánchez, Patricia; Gómez, Claudia (International Journal of Combinatorial Optimization Problems and Informatics, 2016)
Here, an interactive method is proposed to incorporate the preferences of the Decision Maker (DM) into the optimization process and lead the search towards the Region of Interest (ROI). The DM’s preferences are expressed in a reference set and are reflected by an outranking model. This information is used by a multi-criteria sorting method to create selective pressure towards solutions that are satisfactory to the DM. Our method obtains a better characterization of the ROI when compared with the well known NSGA-II and A2-NSGA-III in simple and complex project portfolio problems.